Mengkriminalisasi Greenwashing: Menjawab Tantangan Perlindungan Konsumen di Era Keberlanjutan - Zentoni; Budi Santoso; David M. L. Tobing (Jurnal Litigasi)
Greenwashing is a phenomenon where companies claim their products or policies are environmentally friendly when, in reality, they are not. This phenomenon has grown alongside increasing public awareness of the importance of environmental sustainability. Greenwashing not only harms consumers who are misled by these false claims but also poses a threat to the environment by obscuring corporate responsibility toward sustainability. In the context of criminal law, greenwashing can be categorized as a serious form of environmental fraud; however, many countries still lack clear regulations to address it. As sustainability becomes a central focus across various sectors, the need for stricter regulation and legal enforcement against unethical practices like greenwashing is crucial. This research uses a normative legal method with statutory, conceptual, and comparative approaches. The findings reveal that Indonesia's criminal law is insufficient in addressing greenwashing, which harms both consumers and the environment. Comprehensive legal reform is necessary. Indonesia currently lacks specific regulations that criminalize greenwashing, making it essential to revise laws such as the Criminal Code, the Consumer Protection Law, or Environmental Law. These reforms should include clear definitions, transparent evidence standards, and strict sanctions, including criminal penalties for companies found guilty. Several countries, such as France, Germany, Canada, and Australia, have taken proactive steps by tightening regulations and law enforcement. Indonesia can learn from these countries to develop a more responsive legal system. Adopting international standards and harmonizing regulations across countries is also important to address global challenges that allow multinational companies to evade responsibility....